Resilience and criminal behaviour involvement among juveniles in Malaysia: a case study - Ruslan, Aisyatul Radhiah; Che Hassan, Norlizah; Mat Yusoff, Mohd Azmi (Human Resource Management Academic Research Society, 2020)
Adolescence is perceived as a critical stage in human life. The well-being of adolescents is related to the level of resilience and criminal behaviour involvement among them. Recently, adolescents’ level of involvement in delinquency has increased. Therefore, the purpose of this study was to determine the relationship between adolescent level of resilience and criminal behaviour involvement. The study was based on the quantitative method with correlational design using questionnaires adapted from the previous studies. The research instrument of the Personal Resilience Questionnaire was adapted from Warner (2009), and the Youth Delinquency questionnaire from Rozumah (2003). A pilot study was conducted with the Cronbach Alpha score for the Personal Resilience Questionnaire was 0.85 and the delinquent behavioural questionnaires was 0.73. The sample used in this case study were students in Integrity School (Kajang Prison), Selangor. A simple random sampling was used with a sample size of 132 students chosen as the respondents. The findings indicated that the highest percentage of respondents is at medium level (criminal behaviour), while the lowest percentage is at the low level (criminal behaviour). It was also found that these adolescents have low level of personal resilience. The study also found that there is a significant relationship between the level of resiliency and criminal behaviour involvement. This study gives contribution to the field of study by suggesting that relevant parties can have better understanding on the aspects of adolescent resilience, thus develop effective preventive measures for them.